Low Recruitment of Native Trees in a Deciduous Forest Associated with Japanese Barberry (Berberis thunbergii) Invasion. (6th February 2018) - Link, Arthur F.; Turnblacer, Trey; Snyder, Cierra K.; Daugherty, Sarah E.; Utz, Ryan M.
Abstract: Invasive plants may dramatically impact forest ecosystems by establishing dense populations and suppressing the recruitment of native tree species. One invasive shrub currently spreading throughout eastern deciduous forests of North America, Japanese barberry ( Berberis thunbergii DC), may be limiting tree recruitment in stands where it invades. Once established, B. thunbergii becomes densely populated within forest understories and suppresses native plants by competing for limited resources, altering soil conditions, and changing the understory microclimate. To quantify native seedling inhibition caused by B. thunbergii invasion, we conducted an observational study on seedling abundance within forest plots that were either invaded or not invaded by B. thunbergii and used survey data to generate Bayesian models of native seedling densities along gradients of increasing B. thunbergii stem counts and aboveground plant dry mass. Model outputs predicted that B. thunbergii –invaded plots had 82% lower seedling densities compared with uninvaded plots. Native tree seedling densities were very low even in areas with moderate B. thunbergii density, suggesting that reduced tree seedling densities are observed even at low densities of invasion. Our findings indicate that forests invaded with B. thunbergii harbor substantially lower densities of native tree seedlings, with potentially significant long-term consequences for forest ecological integrity, biodiversity, and ecosystem services.